Association between ABO blood groups and their clinical indices during COVID-19 infection - Sreekanth Patnam; Sudha Ranganathan; Nagalla Balakrishna; Anula Divyash Singh; Rajeswari Koyyada; Swarna Deepak Kuragayala; Prerna Bommasamudram; Sasidhar Venkata Manda; Polati Vishnu Rao (Asian Journal of Transfusion Science)
AIM: To explore the association of ABO blood groups with COVID-19 severity, mortality, hospital stay, and their clinical indices. METHODS: Retrospective clinical data from 185 COVID-19 patients were stratified into four-time points based on their survival status and length of hospital stay (<8> days). Chi-square tests, two-way ANOVA, multinomial logistic regression analyses, and multivariate logistic regression analyses were used to study their associations, strengths, and risk. RESULTS: The frequency distributions of blood groups among COVID-19 patients were A (19.45%), B (26.48%); AB (7.02%); and O (47.02%), respectively. Even though patients in the O-blood group had the highest infection rate (47.02%), patients in the AB blood group had the maximum severity and mortality and patients in the A-blood group had the most negligible mortality. The mean overall survival time among different blood groups was O (23), A (19), B (24), and AB (17) days. Mean platelet count (%), aggregate index of systemic inflammation (AISI), Platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and hospital stay were increased (P < 0.005) in the AB blood group among survivors >8 days. Total leukocyte count (TLC) cells/mm3 levels were increased among nonsurvivors in <8 days in the AB blood group (P < 0.005). Lactate dehydrogenase U/L was increased (P < 0.005) in A blood group of nonsurvivors of <8 days. CONCLUSIONS: Even though O blood group patients had the highest infection rate, AB group patients had the most severe disease accompanied by the least survival. Higher (AISI, PLR, SII, and higher TLC) were associated among the survivors of the AB blood group.